Melatonin attenuates postovulatory oocyte dysfunction by regulating SIRT1 expression. Issue 1 (July 2018) - Yang, Qingling; Dai, Shanjun; Luo, Xiaoyan; Zhu, Jing; Li, Fangyuan; Liu, Jinhao; Yao, Guidong; Sun, Yingpu
Abstract : The quality of postovulatory metaphase II oocytes undergoes a time-dependent deterioration as a result of the aging process. Melatonin is considered to be an anti-aging agent. However, the underlying mechanisms of how melatonin improves the quality of postovulatory aged oocytes remain largely unclear. In this study, by using mouse model, we found that there were elevated reactive oxygen species levels and impaired mitochondrial function demonstrated by reduced mitochondrial membrane potential and increased mitochondrial aggregation in oocytes aged 24 h, accompanied by an increased number of meiotic errors, unregulated autophagy-related proteins and early apoptosis, which led to decreased oocyte quality and disrupted developmental competence. However, all of these events can be largely prevented by supplementing the oocyte culture medium with 10 −3  M melatonin. Additionally, we found that the expression of sirtuin family members (SIRT1, 2 and 3) was dramatically reduced in aged oocytes. In addition, in vitro supplementation with melatonin significantly upregulated the expression of SIRT1 and antioxidant enzyme MnSOD, but this action was not observed for SIRT2 and SIRT3. Furthermore, the protective effect of melatonin on the delay of oocyte aging vanished when the SIRT1 inhibitor EX527 was used to simultaneously treat the oocytes with melatonin. Consistent with this finding, we found that the postovulatory oocyte aging process was markedly attenuated when the oocytes were treated with the SIRT1 activator SRT1720. In conclusion, our data strongly indicate that melatonin delays postovulatory mouse oocyte aging via a SIRT1–MnSOD-dependent pathway, which may provide a molecular mechanism support for the further application of melatonin in the assisted reproductive technology field.